Modification of cereal and tuber waxy starches with radio frequency cold plasma and its effects on waxy starch properties. (1st November 2019) - Okyere, Akua Yeboah; Bertoft, Eric; Annor, George Amponsah
Highlights: Final viscosities for all three starches significantly decreased after plasma treatment. Resistant starch significantly increased in waxy maize and potato starch after plasma treatment. Possible formation of V-type single helices was observed in waxy maize and rice as indicated by NMR. Starch damage increased significantly after plasma treatment in waxy potato and maize. Abstract: The use of carbon dioxide-argon gas radio frequency cold plasma in modifying waxy rice, maize and potato was explored in this paper. Treatment with plasma at 120 W or 0 W (carbon dioxide-argon gas mixture only) resulted in significant increases in the enthalpy of gelatinization of all three waxy starches. Treatment with plasma or gas resulted in a significant increase in the resistant starch content of maize and potato with rice increasing only after gas treatment. Significant decreases were observed in the setback and final viscosities after 120 W treatment in all starches. Plasma and gas treatment resulted in a 5.5% and 2.8% decrease in crystallinity of potato but not rice and maize starch. NMR results showed the presence of V-type single helices in mostly maize and rice starches. Carbon dioxide-argon radio frequency cold plasma served as a useful tool in modifying the properties of all three waxy starches.